A study of factors associated with the farmers attitudes toward the agricultural extension service in the mukim of Simpor, district of Kuala Muda, state of Kedah, West Malaysia, 1970 - Nayan Ariffin, 1934- (Serdang : Universiti Pertanian Malaysia, 1970)
28